Factor associated with timely initiation of complementary feeding practices among children aged 6-23 months in rural communities of Dhanusha, Nepal (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Six months to 2 years of age is known as the transition period and is a component of the critical window of opportunity to support the survival and optimal growth of child. World Health Organization (WHO) recommends that the mothers should start soft, semi-solid, or solid food for their infant at the age of 6 months. Therefore, this study aimed to assess the timely initiation of complementary feeding practices among children aged 6-23 months in rural municipalities of the Dhanusha district of NepalMaterial and Methods: A community-based cross-sectional study was conducted in rural municipalities of Dhanusha district, Province 2 of Nepal between February and March 2021.A sample of 366 mothers having children aged 6-23 months were selected using multi-stage cluster sampling. Multivariable logistic regression analysis was applied to explore the timely initiation of complementary feeding practices among children.Results: The study found that more than half 54.9% of the respondent timely initiated complementary feed to their child. Timely initiation of complementary feeding was 1.68 times higher among male children than a female child. Similarly, the mothers who initiated breast milk within one hour and exclusively breastfed were 1.64 times and 4.19 times more likely to initiate complementary feeding than those who had initiated breast milk one hour and more and not exclusively breastfed.Conclusions: More than half of the mother’s initiated timely complementary feed to their child. Sex of the child, initiation of breastfeeding within one hour, and exclusive breastfeeding practices were significantly associated with timely initiation of complementary feeding. Therefore, more efforts should be focused to raise awareness regarding age-appropriate feeding among mothers who may increase the timely initiation of complementary feeding and hence reduce the burden of malnutrition and related complications